Peningkatan Efektivitas untuk Perusahaan Pigura - Timotius Limanto; I Nyoman Sutapa (Jurnal Titra, 2021)
Hartono Frame is Frames company that has a problems about delays in order production due to the absence of order production scheduling control and the amount of time wasted due to a lot of movement to find and repair tools. Then there is the loss of finished products in the warehouse due to the messy arrangement of finished goods so that employees forget to put the place and goods are sometimes tucked in a pile of other goods. Improvements made using the DMAIC method by identifying problems, measuring problems, finding root causes, dealing with existing problems, and controlling the improvements that have been given. Improvements made are design of job descriptions, design of production schedules, and given 5S method for the assembly room and warehouse so that the assembly process is easy to do and the goods in the warehouse are easy to find. The results obtained after the repair are an increase in effectiveness in the accuracy of finished products according to the previous order deadline which was 70% to 90% and an increase in the effectiveness of storing goods in the finished goods warehouse which used to lose an average of 12 items to 6 per day.